Hospital Preparedness Analysis in Disaster Management : Literature Review - Chairiyah, Tengku Armita; Hasibuan, Abdurrozzaq (RADINKA JOURNAL OF HEALTH SCIENCE, 2024)
Under Act No. 44 of 2009, hospitals have a responsibility to actively engage in disaster situations, provide services to victims as they can, and have an accident prevention and disaster management system. This research aims to find out how prepared some hospitals are in disaster management based on some library studies. The preparation of this article uses a method of systematic literature review using 10 articles from 2019 to 2024 from search databases, namely Google Scholar, Garuda, Sage Journals, and ScienceDirect. Although hospitals have policies and standard operational procedures to cope with disasters, the findings suggest that their implementation by health personnel is not optimal. Although disaster response teams, K3RS teams, and abuse teams have been formed, education and training efforts are still not at their maximum. Hospitals are important in disaster management, but many still need improvements such as special guidelines, infrastructure, and intensive training. Preparedness includes planning, organization, movement, control, and recovery. Ready hospitals have emergency response teams, training programs, and early warning systems.